Social Philosophical Analysis Of Youth Moral Culture And Attitudes To The Older Generation In Society - Akhmadiev Nuriddin Mukhutdinovich; Eshboyev Akramjon Karimjonovich (Euro Asian Journal Publishing, 2024)
In this article, the moral culture of youth and the role of the older generation in society are analyzed as important factors determining the development of New Uzbekistan. In it, it is explained that the country's cultural, economic and political development is aimed at ensuring the country's cultural, economic and political development through reforms aimed at the youth's thinking in society and targeting the representatives of the older generation
Keywords: civil society; new development